1999
DOI: 10.1023/a:1026437731354
|View full text |Cite
|
Sign up to set email alerts
|

Dose-finding study of epidoxorubicin and docetaxel as first-line chemotherapy in patients with advanced breast cancer

Abstract: SummaryBackground: Anthracyclines and taxanes are the most active drugs against breast cancer and the search after their optimal combination is under intensive investigation in both the advanced and early disease settings. A dose-finding study of epidoxorubicin (E) and docetaxel (D) was conducted in advanced breast cancer (ABC) to define the maximum tolerated dose (MTD) of the combination with and without granulocyte colony-stimulating factor (G-CSF) support and to characterise its toxicity and activity profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…In the phase II study performed by Mavroudis et al (2000), treatment with 70 mg m À2 of epirubicin and 90 mg m À2 of docetaxel resulted in an ORR of 66% with a median TTP of 11 months. The combination of docetaxel and epirubicin without G-CSF support resulted in febrile neutropenia in approximately 15% of cycles in a trial by Pagani et al (1999) and in 4 and 7% of cycles in the trials by Morales et al (2004) and Mavroudis et al (2000), respectively. In our study, febrile neutropenia was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…In the phase II study performed by Mavroudis et al (2000), treatment with 70 mg m À2 of epirubicin and 90 mg m À2 of docetaxel resulted in an ORR of 66% with a median TTP of 11 months. The combination of docetaxel and epirubicin without G-CSF support resulted in febrile neutropenia in approximately 15% of cycles in a trial by Pagani et al (1999) and in 4 and 7% of cycles in the trials by Morales et al (2004) and Mavroudis et al (2000), respectively. In our study, febrile neutropenia was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…Several phase I studies were performed, with combinations including docetaxel and doxorubicin (Misset et al, 1999), docetaxel+doxorubicin+cyclo-phosphamide (Nabholtz et al, 1997), docetaxel and epidoxorubicin (Pagani et al, 1999), docetaxel and cisplatin (Crown et al, 1997), docetaxel and vinorelbine (Fumoleau et al, 1996b), and docetaxel and 5-fluorouracil (Lortholary et al, 1997).…”
Section: Docetaxelmentioning
confidence: 99%
“…The dose escalation used, number of patients treated and cycles administered, together with the incidence of febrile neutropenia, are shown in Table 1 [22,23]. Epirubicin was administered as a 15-minute infusion and followed 1 hour later by the 1-hour infusion of docetaxel.…”
Section: Dose-findingmentioning
confidence: 99%
“…Including the 20 patients treated in the dose-finding study and 50 in the phase II trial, a total of 70 patients received the combination of 75 mg/m 2 docetaxel and 90 mg/m 2 epirubicin [22,23]. The dominant site of disease was visceral in 38 patients (54%).…”
Section: Combined Seriesmentioning
confidence: 99%
See 1 more Smart Citation